Adsorption performance of Enterobacter cloacae towards U(VI) ion and application of Enterobacter cloacae/carbon nanotubes to preconcentration and determination of low-levels of U(VI) in water samples. (January 2023) - Mohammadzadeh, Alireza; Kadhim, Mustafa M.; Taban, Talib Zeedan; Baigenzhenov, Omirserik; Ivanets, Andrei; Lal, Basant; Kumar, Naveen; Hosseini-Bandegharaei, Ahmad
Abstract: Keeping the high potential of some microorganisms in adsorption of radionuclides in view, the adsorption properties of Enterobacter cloacae towards uranium were attentively scrutinized, and then it was used for preconcentration of uranium in different samples, using Enterobacter cloacae /carbon nanotube composite. First, using ultrasonic agitation, the effects of operational factors on biosorption of uranium on the inactive Enterobacter cloacae were appraised and modeled by central composite design, and a comprehensive study was performed on the equilibrium, kinetics, thermodynamic, and selectivity aspects of biosorption. The optimization studies along with the evaluations of the adsorption properties revealed that Enterobacter cloacae have a high affinity for fast and selective biosorption of uranium ions, at pH 5.1. Second, the Enterobacter cloacae /carbon nanotube was synthesized, characterized, and utilized for preconcentration of uranium in different samples, using a mini-column packed with the composite. The optimization of operational factors on recovery of uranium, using the central composite design, showed that uranium can be quantitively adsorbed at a sample flow rate lower than 4.5 mL min −1 and the desorption could be accomplished with 3.0 mL HCl 0.6 M solution. Finally, the mini-column was exploited for preconcentration and determination of uranium in different samples. The results revealed the low detection limit (0.015 μg.L −1 ), high precision (RSDs ≤3.92%), and good accuracy of the proposed procedure. Graphical abstract: Because of the adequate adsorption properties of Enterobacter cloacae towards uranium, it was utilized for preconcentration of uranium in different samples, using Enterobacter cloacae /carbon nanotube composite. Image 1 Highlights: Adsorption properties of Enterobacter cloacae for uranium were attentively scrutinized. Effects of operational factors on the process were appraised by CCD. Enterobacter cloacae /MWCNTs composite was utilized for preconcentration of uranium. The results showed the efficiency of the proposed procedure for determination of U(VI).